Investigation of the Autoregulator-Receptor System in the Pristinamycin Producer Streptomyces pristinaespiralis - Handel, Franziska; Kulik, Andreas; Mast, Yvonne (Frontiers in Microbiology, 2020)
Pristinamycin biosynthesis in Streptomyces pristinaespiralis is governed by a complex hierarchical signaling cascade involving seven different transcriptional regulators (SpbR, PapR1, PapR2, PapR3, PapR4, PapR5, and PapR6). The signaling cascade is triggered by γ-butyrolactone (GBL)-like effector molecules, whereby the chemical structure of the effector, as well as its biosynthetic origin is unknown so far. Three of the pristinamycin transcriptional regulators (SpbR, PapR3, and PapR5) belong to the type of γ-butyrolactone receptor (GBLR). GBLRs are known to either act as ‘real’ GBLRs, which bind GBLs as ligands or as ‘pseudo’ GBLRs binding antibiotics or intermediates thereof as effector molecules. In this study, we performed electromobility shift assays (EMSAs) with SpbR, PapR3, and PapR5, respectively, in the presence of potential ligand samples. Thereby we could show that all three GBLRs bind synthetic 1,4-butyrolactone but not pristinamycin(-derived) substances as ligand, suggesting that SpbR, PapR3, and PapR5 act as ‘real‘ GBLRs in S. pristinaespiralis. Furthermore, we identified a cytochrome P450 monooxygenase encoding gene snbU as potential pristinamycin effector biosynthesis gene. Inactivation of snbU resulted in an increased pristinamycin production, which indicated that SnbU has a regulatory influence on pristinamycin production. EMSAs with culture extract samples from the snbU mutant did not influence the target binding ability of SpbR, PapR3, and PapR5 anymore, in contrast to culture supernatant samples from the S. pristinaespiralis wild-type or the pristinamycin deficient mutant papR2::apra, which demonstrates that SnbU is involved pristinamycin effector synthesis.